Silymarin treatment and reduction of liver enzyme levels in non-alcoholic fatty liver disease: a case report - Tanyaporn Chantarojanasiri (BioExcel Publishing Ltd, 2023)
Non-alcoholic fatty liver disease (NAFLD) is one of the most frequent chronic liver disorders worldwide. It is closely associated with metabolic syndrome components, including type 2 diabetes, hyperlipidaemia and obesity. To date, no effective drug treatment is available for NAFLD but several clinical trials suggested that silymarin, the active milk thistle extract, has well-documented antioxidant and hepatoprotective properties. In this case report, silymarin 140 mg twice daily decreased liver enzyme activity with a good safety profile in a patient with NAFLD and overweight, supporting silymarin as a promising supportive intervention aimed at normalizing liver activity in NAFLD. This article is part of the Current clinical use of silymarin in the treatment of toxic liver diseases: a case series Special Issue: https://www.drugsincontext.com/special_issues/current-clinical-use-of-silymarin-in-the-treatment-of-toxic-liver-diseases-a-case-series